The Influence of Islamic Learning and Parental Support on Students' Religious Moral through Emotional Intelligence - Khoiriyah, Ni’amatul; Mizani, Zeni Murtafiati; Daryono, Rihab Wit (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
This study aims to analyze Islamic Learning and Parental Support for Students' Religious Morals in MAN 1 Ngawi. A quantitative approach was used with the survey method, which was conducted retrospectively to test the construction of the Student Religious Moral variable. This research applied a probability sampling method to select a sample of 278 from 300 students at MAN 1 Ngawi. Data collection was done through Google Forms. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that all indicators met the requirements of validity and reliability. Islamic Learning and Parental Support significantly impacted Students' Religious Morals. Emotional Intelligence mediates the relationship between Islamic Learning and parental support with Student Religious Morals. The study concluded that Islamic Learning and Parental Support contribute significantly to Students' Religious Morals. The role of emotional intelligence in mediating the influence of Islamic learning and parental support on students' religious morals has essential implications in religious education and the formation of children's moral character. These implications highlight that the ability to understand and manage emotions can influence learning acceptance, while parental support can strengthen the process of forming religious morals. Suggestions and recommendations include contextual studies that influence the development of students' emotional intelligence in Islamic Learning and Parental Support that supports the formation of Students' Religious Morals.